FORECAST OF ENTRANCE TICKETS UPT.KEBUN RAYA UNMUL SAMARINDA (KRUS) SAMARINDA - Eka Yudhyani, RISMA SAFITRI, Theresia Militina, (EKONOMIA, 2015)
This research aims to knowing its rise or fall forecasting sales of entrance tickets which is conducted by  UPT.Kebun Raya Unmul Samarinda 2015.            As a basis in this study the authors take theories and concepts of experts of economics associated with the theory of the budget,forecasting.as for as the base support this research is forecasting,marketing.            In the research it is presented by hypothesis that is “it is suspected ases by forecasting sales tickets which is conducted by UPT.Kebun Raya Unmul Samarinda           2015 the experience of increase.            From data result which dihim also writer in the research,writer calculate sale  entrance tickets UPT.Kebun Raya Unmul Samarinda From year 2010 reaches 2014.after calculate and know turnover entrance ticket,writer use analyzer in the form of statistic use formula method Least Square.            Form result calculate which performed by writer to forecast entrance ticket UPT.Kebun Raya Unmul Samarinda for year 2013 Rp.1.143.902.700 and year 2014 Rp.1.295.510.000 the experience of increase 9,04% from sale year 2013.while for forecasy of year 2014 Rp.1.295.510.000 and year 2015 Rp.1.499.785.378 the experience of increase 12,02% for sale of year 2014